2020
DOI: 10.3762/bjnano.11.164
|View full text |Cite
|
Sign up to set email alerts
|

Nanocasting synthesis of BiFeO3 nanoparticles with enhanced visible-light photocatalytic activity

Abstract: In this work, monodisperse BiFeO3 nanoparticles with a particle diameter of 5.5 nm were synthesized by a nanocasting technique using mesoporous silica SBA-15 as a hard template and pre-fabricated metal carboxylates as metal precursors. To the best of our knowledge, the synthesized particles are the smallest BiFeO3 particles ever prepared by any method. The samples were characterized by X-ray powder diffraction, transmission electron microscopy and UV–vis diffuse reflectance spectroscopy. The phase purity of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…The determined band gap energy of 2.22 eV is considerably smaller, and thus, redshifted when compared to bulk BiFeO . As we discussed in detail previously, a meaningful comparison of band gap values of different BiFeO samples is not always possible as morphology, size, phase purity, as well as oxygen vacancies have a strong impact on the band gap [ 36 , 40 ]. The redshift is often a result of the strained nature of nanosized materials as well as symmetry breaking in high-surface-area materials.…”
Section: Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The determined band gap energy of 2.22 eV is considerably smaller, and thus, redshifted when compared to bulk BiFeO . As we discussed in detail previously, a meaningful comparison of band gap values of different BiFeO samples is not always possible as morphology, size, phase purity, as well as oxygen vacancies have a strong impact on the band gap [ 36 , 40 ]. The redshift is often a result of the strained nature of nanosized materials as well as symmetry breaking in high-surface-area materials.…”
Section: Results and Discussionmentioning
confidence: 99%
“…The photocatalytic activity of the synthesized hollow spheres is much enhanced compared to bulk material and BiFeO materials free of surface defects [ 23 ]. Furthermore, unsupported BiFeO nanoparticles with a large surface area and an average diameter of approximately 5.5 nm were shown to have a degradation efficiency of approximately during the same time period [ 40 ]. In fact, as previously reported that the photocatalytic activity of BiFeO actually decreases with a reduction in particle size as a result of crystal defects and local distortions [ 36 , 40 , 41 ].…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…BiFeO 3 , one of those Bi-based photocatalysts, has been the subject of intensive research in recent years because it is the only naturally occurring magnetoelectric material with ferromagnetic and ferroelectric properties at room temperature [ 39 , 75 , 87 89 ]. Bismuth ferrite has a distorted rhombohedral perovskite structure (ABO 3 ), where A is a corner cation, B is a body-centred middle atom, and O is an oxygen atom or anions attached to the crystal faces.…”
Section: Reviewmentioning
confidence: 99%
“…In more detail, bismuth ferrite materials (BiFeO 3 ) are characterized by ferroelectricity and ferromagnetic features [167]. They have been explored as nanofibers [168], nanoparticles [169][170][171], nanosheets [172], nanotubes [173], microspheres [174], and nanorods [175], exploiting their magnetic properties and the 2.2 eV bandgap. Li et al [173] compared the photocatalytic behaviour of BiFeO 3 in the form of nanoparticles, nanofibers, and hollow nanotubes, discovering the superior photoactivity of the latter due to the ultra-thin wall thickness and unique material structure.…”
Section: Eco-friendly Materials Used To Treat "Model Pollutants"mentioning
confidence: 99%